'Back to the future': Thinking with Hannah Arendt (1906–1975) and Alec Clegg (1909–1986) on the promise of education. (4th March 2023) - Wood, Margaret; Pennington, Andrew; Su, Feng
ABSTRACT: This article analyses, mingles and blends divergent and complementary strands from the thinking of Hannah Arendt (1906–1975) and Sir Alec Clegg (1909–1986), two contemporaneous but different influential public figures and thinkers in the post-World War Two period. The paper uses these strands to construct a critique of the current colonisation of education by neo-liberal economic logics and performative architecture. Their ideas emerge as bulwarks against populist discourse, reductivist, authoritarian framings of education policy and the restrictive and prescriptive direction of education practice. Conceptions of pluralism, imagination, the location of children and young people's perspectives in the adult world, citizenry and engagement with the world are illuminated for their refreshing power to replenish and sustain the conditions for an education that supports human flourishing.